The primary abundance of chondrules in CI chondrites - Kimura, Makoto; Ito, Motoo; Monoi, Akira; Yamaguchi, Akira; Greenwood, Richard C. (2024)
CI chondrites are the most significant extra-terrestrial samples for estimating the composition of primordial materials in the Solar System. However, CIs lose many primary features because of heavy parent body aqueous alteration. However, CI and CI-related Ryugu particles contain small amounts of relict anhydrous minerals, indicating primary occurrences of chondrules and refractory inclusions. In this study, we estimated the primordial abundance of chondrules in CIs from calculations of the bulk major element compositions. The constraints for the calculation were as follows: 1) CI chondrites primarily comprised chondrules, refractory inclusions, opaque minerals, and a matrix similar to other carbonaceous (C) chondrites. 2) The chemical compositions of these components were similar to those of the unaltered C chondrites. 3) The primary matrix composition of the CI was close to the mean bulk composition. 4) The alteration occurred isochemically. We used the mean major elemental compositions of chondrules and refractory inclusions in an almost unaltered chondrite, Y-81020, CO3.05. Our results were within the range of previously reported CI bulk chemical compositions in the case where chondrule abundances are ≲10 wt%. We also calculated the bulk chemical composition of Tagish Lake, ungrouped C2, which primarily contained ≲20 wt% chondrules. The CI chondrites and Tagish Lake were formed in the outer Solar System. The low primary abundance of chondrules in CIs is closely related to the formation conditions of chondrules in such regions. We suggest that dust with abundant ice and minor chondrules accreted onto the parent bodies of the CI and Tagish Lake in the outer Solar System. Primordial chondrule abundance is the key to clarifying the physical and chemical conditions and evolution of the early Solar System.